Assessment of the community wildlife management partnership : a case study of the Uganda Wildlife Authority and local communities around Mount Elgon National Park, Uganda - Hamidah, Namatovu (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015